Out of the pocket : football, fatherhood, and College GameDay Saturdays - Herbstreit, Kirk; Wojciechowski, Gene (Atria Books, 2021)
The face and voice of college football, in this riveting and revealing memoir, takes readers behind the scenes, describing how a combination of hard work, perseverance and a little luck landed him on the set of ESPN's iconic College GameDay.